The Apologizing Utterances of the Characters in “Failure to Launch” Movie - Padmasari, Arumtyas Puspitaning; Simanjuntak, Nensy Megawati (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Communication is essential in expressing the desires of humans, as their lives are intertwined with it. Producing speech acts is what happens when we interact with others. This study employed a descriptive qualitative approach to analyze qualitative data. The movie "Failure to Launch" is where the data comes from. This study used data collection techniques such as observing, analyzing visuals, and researching in libraries to find literature sources. Based on the findings and analysis, the researcher observed 9 instances of apologizing speech in 6 scenes from the movie "Failure to Launch". The characters in the movie use apology statements to convey their emotions. The emotions depicted include feelings of apology, compassion, remorse (guilt), and condolences.